Planning for Empowerment People's Campaign for Decentralised Planning in Kerala - T M Thomas Isaac K N Harilal (Economic and Political Weekly January 4-11, 1997, 1997)
Despite the acclaimed advantages of decentralisation of planning and repeated commitments made in its favour, the planning process in India has remained a highly centralised affair. None of the departmental exercises -so-called district plans, block level planning or area level programmes - has been able to ensure genuine planning from below, sensitive as such planning should be to complex local-specific problems and felt needs of the people. In the above context, the newly constituted Kerala State Planning Board resolved to initiate a People 's Campaign to empower panchayats and municipal bodies to draw up Ninth Plan schemes within their respective areas of responsibility. It is the Planning Board's expectation that 35 to 40 per cent of Kerala's Ninth Plan will consist of schemes formulated and implemented from below. While it is, of course, premature to attempt an assessment of the ongoing People's Campaign, the all-round support that the Campaign has received suggests some observations regarding its far-reaching implications